2015
DOI: 10.15346/hc.v2i1.2
|View full text |Cite
|
Sign up to set email alerts
|

Crowdsourcing and the Semantic Web: A Research Manifesto

Abstract: Our goal with this research manifesto is to define a roadmap to guide the evolution of the new research field that is emerging at the intersection between crowdsourcing and the Semantic Web. We analyze the confluence of these two disciplines by exploring their relationship. First, we focus on how the application of crowdsourcing techniques can enhance the machine-driven execution of Semantic Web tasks. Second, we look at the ways in which machine-processable semantics can benefit the design and management of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 49 publications
(35 reference statements)
0
30
0
Order By: Relevance
“…There exist several synergies between the fields of Semantic Web and Human Computation that open up a number of avenues for research [40].…”
Section: Synergies Of Semantic Web and Human Computation Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…There exist several synergies between the fields of Semantic Web and Human Computation that open up a number of avenues for research [40].…”
Section: Synergies Of Semantic Web and Human Computation Researchmentioning
confidence: 99%
“…The potential benefits at the intersection of Semantic Web and Human Computation fields were already discussed in 2015 [40], where two main possible research branches where identified and documented.…”
Section: Synergies Of Semantic Web and Human Computation Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…Research has been conducted in classifying different types of crowdsourcing initiatives, to predict their success based on project characteristics (Noordegraaf et al, 2014). Sarasua et al (2015) discuss guidelines to how Semantic Web technology can support design and management of crowdsourcing projects, while Yadav and Darlington (2016) introduce guidelines for designing platforms hosting multiple projects. Methodology papers that outline steps to successfully run a crowdsourcing campaign are however scarce.…”
Section: Related Workmentioning
confidence: 99%